(untitled) (Heritage, 2023)
The beginnings of contemporary Serbian art in Kosovo and Metohija are related to the establishment of the first educational institutions in this area, where generations of students and art studenst were educated. And overview of the development of contemporary art in Kosovo and Metohija can be traced back to 1949, when the High School of Art was founded in Peć. This school becomes a nursery of talents and a center of artistic development, imrovement and shaping of artistic reality and Kosovo and Metohija. After that, the development of art education was infuenced by the establishment of the Higher Pedagogical School in Pristina in 1962. The conception of this educational institution included the formation of the Fine Arts Group, where young artists were successfully trained. The Academy of Arts in Pristina was re – established in 1973 an it had the following educational courses painting, sculpture, graphics and graphic design. The Academy played a key role in the development of the art scene in the province, educating young artists and future art teachers. Since the school year 1986/87, the Academy was reorganized and continued to work as the Faculty of Arts in Pristina. The most difficult period in the history of university art education in the province ocurred due to the war events in 1999, when the professors and students of this higher education institution were expeled. The facultys infastructure, teaching space and studios were usurped, and most of works of art were looted and destroyed. The Faculty of Arts was then moved first to central Serbia, and cince 2001. It has been working in Zvečan , i.e Kosovska Mitrovica.